Neural substrates involved in anger induced by audio-visual film clips among patients with alcohol dependency. Issue 1 (December 2017) - Park, Mi-Sook; Lee, Bae; Sohn, Jin-Hun
Abstract Background Very little is known about the neural circuitry underlying anger processing among alcoholics. The purpose of this study was to examine the altered brain activity of alcoholic individuals during transient anger emotion. Methods Using functional magnetic resonance imaging (fMRI), 18 male patients diagnosed with alcohol dependence in an inpatient alcohol treatment facility and 16 social drinkers with similar demographics were scanned during the viewing of anger-provoking film clips. Results While there was no significant difference in the level of experienced anger between alcohol-dependent patients and non-alcoholic controls, significantly greater activation was observed in the bilateral dorsal anterior cingulate cortex (dACC) and the right precentral gyrus among alcoholic patients compared to the normal controls. Conclusions In summary, specific brain regions were identified that are associated with anger among patients with alcohol dependency.